1942
DOI: 10.1128/jb.44.6.667-672.1942
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Beading of the Tubercle Bacillus Stained by the Ziehl-Neelsen Technique

Abstract: Koch first described the beaded forms of the tubercle bacillus and regarded the beads as evidence of spore formation. Later investigators attempted to correlate the beaded forms with the age and the virulence of the microorganism. These studies, however, have not been fully confirmed. In the present paper, data will be submitted to show that the beads exhibited by tuberele bacilli stained with earbol fuchsin are greatly influenced by the preparation of the dve used, by the presence of electrolytes in the syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
6
0

Year Published

1945
1945
1964
1964

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 0 publications
2
6
0
Order By: Relevance
“…In accordance with the work of Yegian and Baisden (1942) and Porter and Yegian (1945) it has been confirmed that beading occurs in the step of the Ziehl-Neelsen procedure in which the smears are washed with water. The action is sudden and independent of the species of acid-fast organism being studied.…”
supporting
confidence: 79%
See 3 more Smart Citations
“…In accordance with the work of Yegian and Baisden (1942) and Porter and Yegian (1945) it has been confirmed that beading occurs in the step of the Ziehl-Neelsen procedure in which the smears are washed with water. The action is sudden and independent of the species of acid-fast organism being studied.…”
supporting
confidence: 79%
“…Therefore, when equal quantities of saturated alcoholic solutions of these dye salts are used to make up the carbol-fuchsin, it is more likely that with the acetate dye salts high enough concentrations of dye will be present to cause a loss in solubility of the phenol than in the case of the chloride. In agreement with this statement is the reported observation (Yegian and Baisden, 1942) that employment of the acetate dye salts to make up carbolfuchsin gave a colloidal suspension instead of a clear solution as in the case when the chloride dye salts were used.…”
supporting
confidence: 77%
See 2 more Smart Citations
“…t;4 dye is removed in the course of the process, and a certain minimum amount of free dye is necessary for precipitation. Yegian and Baisden (1942) have shown that when the concentration of the dye is reduced the beads decrease in size and number but not in density. '-p -.. :.…”
Section: Resultsmentioning
confidence: 99%